Imbalance in the production between vascular endothelial growth factor and endostatin in Kawasaki disease - Takeshita, S (Blackwell Science Inc, 2005)
To investigate whether an imbalance exists in the production between angiogenic and antiangiogenic growth factors in patients with Kawasaki disease (KD), we measured the serum levels of vascular endothelial growth factor (VEGF) and endostatin (ES) in 35 patients with KD, 15 patients with acute febrile diseases (disease controls) and 15 healthy children. KD patients had significantly higher VEGF levels and lower ES levels (P < 0·01) in the acute and subacute phases than the disease control and healthy children. KD patients with coronary artery lesions (CAL, n = 10) had significantly higher VEGF levels and lower ES levels (P < 0·05) in the subacute and convalescent phases than those without CAL (n = 25). The ratios of VEGF/ES in sera of KD patients with CAL were significantly higher (P < 0·05) in the acute and convalescent phases compared to those without CAL. Furthermore, the occurrence of CAL significantly correlated with the VEGF/ES ratio above 10 × 10(−3) in the subacute phase of KD (Odds ratio 17·25, P = 0·005). The findings in the present study indicate that an imbalance exists in the production between VEGF and ES in patients with KD while also suggesting that KD patients with a high VEGF/ES ratio have a significantly greater risk of CAL involvement.